2019
DOI: 10.1111/psyg.12401
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial attributes in psychogeriatric service delivery in the district of Colombo, Sri Lanka

Abstract: Background Mental health is a neglected area within the healthcare systems in developing nations, including Sri Lanka. However, the rapid population aging and the resulting rise in psychological issues among the elderly are becoming major concerns within the country. Therefore, a proper assessment of distribution of mental healthcare facilities within the country is much needed in reducing the unmet need among people with psychological symptoms. In this study, the distribution of mental health services within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…One study shows that a majority of women who previously opted for induced abortions themselves were against the legalization of abortion. The same study demonstrated that this attitude might result from sociocultural and religious beliefs that increased availability of abortion services might promote premarital sexual activity and promiscuity among unmarried youth [15]. Despite the existence of restrictions and inertia, numerous stakeholders concerned about women's health at present, are discussing legislative changes to the abortion law of Sri Lanka [16].…”
Section: Attempted Amendmentsmentioning
confidence: 95%
See 1 more Smart Citation
“…One study shows that a majority of women who previously opted for induced abortions themselves were against the legalization of abortion. The same study demonstrated that this attitude might result from sociocultural and religious beliefs that increased availability of abortion services might promote premarital sexual activity and promiscuity among unmarried youth [15]. Despite the existence of restrictions and inertia, numerous stakeholders concerned about women's health at present, are discussing legislative changes to the abortion law of Sri Lanka [16].…”
Section: Attempted Amendmentsmentioning
confidence: 95%
“…One such study estimated the annual national figure for induced abortion between 125,000 to 175,000 [28]. This study was conducted in the 1990s and a subsequent study in the year 2000 estimated 240,170 annual induced abortions, in other words, a daily rate of 658 and an induced abortion ratio of 741 per thousand women [15]. In 2007, a study using Bogart's' model predicted an induced abortion rate of 0.087 per woman which is a substantial rise from 0.035 per woman in 1993 [29].…”
Section: Abortion Practice In Sri Lankamentioning
confidence: 99%
“…Although the national contraceptive prevalence rate in the country is high, with 65% of the women using some form of contraception (4), unintended pregnancies still occur and some women resort to unsafe abortions (5) The estimated number of abortions performed in a year, ranges from 125 000 to 175 000 in restricted settings (6). This rate has increased significantly over the years, as a study conducted in 2000 estimated 658 induced abortions per day, amounting to 240 170 per year and an abortion ratio of 741 per 1000 live births (7). The emergence of medical abortion pills such as misoprostol has changed the practice of abortion in Sri Lanka, making it easier for women to access and self-administer the drug at home (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%